Knowledge Management from a Complex and Transdisciplinary perspective at the San Francisco de Asís Private University - El Alto (Docentes 2.0 Journal, 2020)
The dynamization of the university context from the knowledge management process in the relationship context / academic reality with the context / sociocultural reality, leads to the internal subsystems that make up the university environment can promote innovative processes that facilitate the management of resources and strategies in favor of knowledge management. The research revalues ??academic knowledge, immersed in a set of factors that activate the development of society, where processes of transformation of society are stimulated in order to prevent psychosocial risks with practical actions. involving an entire university community. The research took into account the paradigm of complex thinking, based on the case study as a research method, using the strategic position of the researcher. The involvement of an entire university community contributes to the management of knowledge that is also an articulating axis that allows a breadth of internal decision-making and subsequent continuous linkage with society, making the university a reference space Thanks to the link between the academic context / reality and the sociocultural context / reality mediated by the knowledge management process based on innovation, creativity and the promotion of participatory processes. Knowledge management must be promoted continuously by the authorities, actions that facilitate continuous, participatory and active management; managing to involve all the subsystems that make up the university, resulting in the improvement of the links and types of communication between those involved.
Keywords: Knowledge management process; sociocultural context / reality; academic context / reality; innovation; revitalization